SOME CHARACTERISTICS OF MENTAL ILLNESS, MENTAL DISORDER PREVENTION AND TREATMENT (World Bulletin of Public Health, 2022)
This article discusses mental illness, prevention of mental disorders and some of its features, as well as symptoms, cognitive disorders, measures to get rid of this mental illness and treatment.
Keywords: schizophrenia; depression; phobia; psychiatry